2018
DOI: 10.1002/14651858.cd013207
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care tests detecting HIV nucleic acids for diagnosis of HIV infection in infants and children aged 18 months or less

Abstract: Point-of-care tests detecting HIV nucleic acids for diagnosis of HIV-1 or HIV-2 infection in infants and children aged 18 months or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Since then, there have been new data supporting the diagnostic accuracy of these tests and the clinical benefit when results are provided on the same day with linkage to immediate action-a rapid HIV test and treat approach for infants. A systematic review of 12 studies found the diagnostic accuracy of point-of-care technologies was greater than 98% sensitive and 99% specific [7]. In addition, a recent systematic review on the clinical impact of point-of-care testing identified seven studies that included 37,000 infants across 15 countries in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…Since then, there have been new data supporting the diagnostic accuracy of these tests and the clinical benefit when results are provided on the same day with linkage to immediate action-a rapid HIV test and treat approach for infants. A systematic review of 12 studies found the diagnostic accuracy of point-of-care technologies was greater than 98% sensitive and 99% specific [7]. In addition, a recent systematic review on the clinical impact of point-of-care testing identified seven studies that included 37,000 infants across 15 countries in sub-Saharan Africa.…”
mentioning
confidence: 99%